Fibroblast growth factor-21 prevents diabetic cardiomyopathy via AMPK-mediated antioxidation and lipid-lowering effects in the heart - Yang, Hong (Cell Death Dis, 2018)
Our previous studies showed that both exogenous and endogenous FGF21 inhibited cardiac apoptosis at the early stage of type 1 diabetes. Whether FGF21 induces preventive effect on type 2 diabetes-induced cardiomyopathy was investigated in the present study. High-fat-diet/streptozotocin-induced type 2 diabetes was established in both wild-type (WT) and FGF21-knockout (FGF21-KO) mice followed by treating with FGF21 for 4 months. Diabetic cardiomyopathy (DCM) was diagnosed by significant cardiac dysfunction, remodeling, and cardiac lipid accumulation associated with increased apoptosis, inflammation, and oxidative stress, which was aggravated in FGF21-KO mice. However, the cardiac damage above was prevented by administration of FGF21. Further studies demonstrated that the metabolic regulating effect of FGF21 is not enough, contributing to FGF21-induced significant cardiac protection under diabetic conditions. Therefore, other protective mechanisms must exist. The in vivo cardiac damage was mimicked in primary neonatal or adult mouse cardiomyocytes treated with HG/Pal, which was inhibited by FGF21 treatment. Knockdown of AMPKα1/2, AKT2, or NRF2 with their siRNAs revealed that FGF21 protected cardiomyocytes from HG/Pal partially via upregulating AMPK–AKT2–NRF2-mediated antioxidative pathway. Additionally, knockdown of AMPK suppressed fatty acid β-oxidation via inhibition of ACC–CPT-1 pathway. And, inhibition of fatty acid β-oxidation partially blocked FGF21-induced protection in cardiomyocytes. Further, in vitro and in vivo studies indicated that FGF21-induced cardiac protection against type 2 diabetes was mainly attributed to lipotoxicity rather than glucose toxicity. These results demonstrate that FGF21 functions physiologically and pharmacologically to prevent type 2 diabetic lipotoxicity-induced cardiomyopathy through activation of both AMPK–AKT2–NRF2-mediated antioxidative pathway and AMPK–ACC–CPT-1-mediated lipid-lowering effect in the heart.